2002
DOI: 10.1007/s00436-001-0555-6
|View full text |Cite
|
Sign up to set email alerts
|

Scanning electron microscopy in the investigation of the in vitro hemolytic activity of Trichomonas vaginalis

Abstract: The in vitro hemolytic activity of Trichomonas vaginalis has been previously demonstrated, but the mechanisms involved remain to be elucidated. In this work we used scanning electron microscopy to investigate the contact dependency of the hemolytic phenomenon caused by the parasites. The erythrocytes adhered to the parasites' surface and were phagocytosed. These observations suggest that the contact between T. vaginalis and erythrocytes may be an important mechanism in the injury caused to the erythrocytes. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…In the case of T. vaginalis , cysteine peptidases have been implicated in the virulence [35]–[37], the cytotoxicity [29], the adherence to host cells [35], [36], [38], [39] and the detachment of host cells [40]. Furthermore, their action was associated with nutrient acquisition [37], [41], hemolysis [42] and the evasion of the host immune response [43][45].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of T. vaginalis , cysteine peptidases have been implicated in the virulence [35]–[37], the cytotoxicity [29], the adherence to host cells [35], [36], [38], [39] and the detachment of host cells [40]. Furthermore, their action was associated with nutrient acquisition [37], [41], hemolysis [42] and the evasion of the host immune response [43][45].…”
Section: Introductionmentioning
confidence: 99%
“…Surface proteins are the most extensively studied molecules in trichomonad adhesion, although much controversy remains in the field (2,10). Previous reports suggest that proteins that bind to extracellular matrix components (4,14,16), cysteine proteinases (6,39,42), erythrocyte-specific ligands (17,24,45), and adhesins (3,5) are found to be involved in attachment of parasite to cells. Carbohydrates on the surface of trichomonads have received much less attention, but several studies have shown their potential role in adhesion.…”
mentioning
confidence: 99%
“…the causative agent of trichomoniasis, a serious sexually transmitted infection affecting over 180 million people worldwide, proteases have been implicated as virulence factors (2)(3)(4)(5)(6)(7)(8), as adherence factors (4 -9), as a cell-detaching factor (10), in nutrient acquisition (2,11), and hemolysis (12,13). It has also been suggested that CPs contribute to pathogenesis when released into the host mucosal surface (2,14) and that they may have roles in evasion of the host immune response (14 -18).…”
mentioning
confidence: 99%